Unemployment and precarious work in a southern European country in times of (permanent) austerity - Valadas, Carla (2015)
In spite of all the efforts and political strategies delivered to control high unemployment levels in EU countries culminating in an European Employment Strategy put into force in the late 90’s of the 20th century, unemployment continues to be one of the EU major social problems. In 2013, over 26 million of people were unemployed, 5.5 million people under the age of 25, and more than 12 million had been without work over twelve months. Although we admit that the labour market situation deteriorated in many countries in the wake of the 2008 economic and financial crisis, in countries like Portugal increasing levels of unemployment and precarious work are also the result of structural problems and ill-conceived employment and educational policies, which are themselves in a process of re-commodification. Another initial idea to consider is that there are different (national, regional) configurations of unemployment, due to a combination of agency and structural features. Beyond common, apparently converging patterns, unemployment and precarious work do not have exactly the same meaning, are not addressed the same way nor produce similar results in all Western European capitalist societies. The aim of this paper is to analyse changes in employment and unemployment in a Southern European country within the last fifteen years, from a sociological institutionalism perspective. This means that we aim to apprehend these changes in a certain political, historical context punctuated by the action and forms of organization of diverse social institutions (e.g. governmental agencies, employers and employees associations) that deliver specific policies and perform a given social and political role. In our analysis we are also concerned with the current meaning of sociological concepts such as work and unemployment, because we concede that they are in a process of transformation resulting from significant changes in the organization of social life and in political (and economic) orientations.